2022
DOI: 10.1111/epi.17250
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 vaccine in patients with Dravet syndrome: Observations and real‐world experiences

Abstract: Objective Vaccination against the SARS‐CoV‐2 virus is a primary tool to combat the COVID‐19 pandemic. However, vaccination is a common seizure trigger in individuals with Dravet syndrome (DS). Information surrounding COVID‐19 vaccine side effects in patients with DS would aid caregivers and providers in decisions for and management of COVID‐19 vaccination. Methods A survey was emailed to the Dravet Syndrome Foundation's Family Network and posted to the Dravet Parent & C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 25 publications
3
42
0
Order By: Relevance
“… [5] , [6] , [7] Specific groups of PWE may differ in their vulnerability, for example, a study of 120 patients with Dravet Syndrome found 13% of patients had a self-reported vaccine-associated seizure exacerbation. [8] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… [5] , [6] , [7] Specific groups of PWE may differ in their vulnerability, for example, a study of 120 patients with Dravet Syndrome found 13% of patients had a self-reported vaccine-associated seizure exacerbation. [8] …”
Section: Discussionmentioning
confidence: 99%
“… [11] Furthermore, COVID-19 may be associated with hypoxia, stroke, systemic inflammatory response syndrome and encephalitis, all capable of precipitating acute symptomatic seizures in already vulnerable patients. [8] Therefore the risk of neurological and systemic complications of COVID infections far outweighs the low risk of vaccine-associated seizure exacerbation.…”
Section: Discussionmentioning
confidence: 99%
“…An Italian cohort study, perhaps one of the largest studies, showed that worsening of seizures after vaccination only occurred in 7.65%, mainly in the 7 days following the vaccine administration and these patients usually had a higher mean number of prevaccine seizure frequency 13 . Regarding the issue of vaccination hesitancy and alleged side effects among patients with genetic etiology, a recent study on Dravet's syndrome suggested that vaccination hesitancy was indeed the case, but the risk of seizure worsening was estimated at 13%, with the authors commenting that reassurance should be given to patients, caregivers as well as health care providers about vaccination among patients with epilepsy 14 . These experiences are, in general, in keeping with our current study that the majority of patients with epilepsy will either tolerate the vaccine very well, or have side effects that are likely to be balanced out by the benefit of protection from COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study, Lu and colleagues reported that patients with tuberous sclerosis complex tolerated inactivated COVID‐19 vaccines well with only 25% of them developing mild AEFI. 38 , 39 …”
Section: Discussionmentioning
confidence: 99%